EVALUASI HIBAH BIBIT KAMBING PE UNTUK KESEJAHTERAAN MASYARAKAT KAB. KULON PROGO - Palupi Triska Ambaruti; Any Suryantini; Suprih Sudrajat (JURNAL ILMIAH AGRITAS, 2022)
The purpose of this study was to determine the level of application of the GFP and the level of community welfare of respondents who received PE goat breed grants in Kulon Progo Regency. The basic method in this research was descriptive and quantitative. This research was conducted from July to September 2020 in Kulon Progo Regency, precisely in Samigaluh District and Kokap District. The sample used was 57 respondents; sample selection used was the census method. The basic method of this research was quantitative descriptive analysis to determine the Level of Good Farming Practices (GFP) and the Level of Welfare based on BPS 2014 and Sajogyo 1997. The analytical tool used was a cross table followed by statistical testing. The results of the study stated that the level of implementation of Good Farming Practices (GFP) recipients of PE goat breed grants in Kulon Progo Regency was in the good category; The level of Welfare of recipients of PE goat breed grants in Kulon Progo Regency based on Welfare BPS 2014 is classified as prosperous, and based on Sajogyo 1997, it is classified as sufficient.